The globalization of values: A comparison between Bangladesh and the USA - Khan, Wahiduzzaman; Khan, Md. Zakir Hossain (Asian Accounting and Auditing Advancement, 2010)
Globalization is creating similar environments for younger consumers around the world. With younger individuals being socialized in more similar environments than their parents, the former should have more comparable values than the latter. The goal of the current study was to empirically test this argument. 154 consumers served as voluntary subjects (84 from the USA and 70 from Bangladesh). Questionnaires were administered to respondents for gathering the necessary data. The respondents ranged in age from 19 to 80. Based on data gathered from 120 subjects across two countries, the results support growing similarities in values between younger consumers in comparison to older consumers. These results suggest that marketers might be able to adopt standardized marketing practices with younger individuals, whereas standardization might not have been an option with their parents. JEL Classification Code: D46, F01, M31